THE ROLE OF ANTHROPONYMS IN THE DEVELOPMENT OF WORLD LINGUISTICS (World Bulletin of Social Sciences, 2024)
The composition of proper names in any language is not given once and for all. The repertoire of anthroponyms is changing: some disappear from active use, others are created, and others change their place. Anthroponymy is a section of onomastics that studies anthroponyms (from the Greek anthropos - person and onoma - name) - names of people: personal names, patronymics, surnames, nicknames, pseudonyms, encrypted names, etc.
Keywords: names; others; Anthroponymy; onomastics